The Effect of Information System of Management ERP and Work Environment to Employee Productivity - Mona Turisna Nasution; Andrian Jeefry (PT. EQUATOR SINAR AKADEMIA, 2026)
This research was made to determine the effect of ERP management information systems and work environment on employee work productivity. The method used in this study is causal associative of 26 respondents of PT. X . To measure the questionnaire data used, the data analysis technique used is the validity test, reliability test and classic assumption test using the normality test using the Kolmogorov-Smirnov test and multicollinearity test by looking at VIF. To measure this research the researchers influence the ERP management information system and work environment on productivity using multiple linear regression analysis, determinant analysis, partial T test, simultaneous F test using SPSS 20 software. The results revealed a partial T test that the management information system partially influences work productivity. The work environment partially influences work productivity, whereas based on the simultaneous F test of the ERP management information system and work environment together it influences work productivity. So it can be concluded that the better the performance of the company's ERP management information system and the better the work environment, the higher the level of employee productivity.